Еще об авторстве статьи «Выставка в Академии художеств за 1860–61 год», атрибутируемой Достоевскому [Revisiting the Problem of Authorship of the Article “Vystavka v akademii khudozhestv za 1860–61 god”: Should We Attribute It to Dostoyevsky?] - Balakin, Alexei (Slavica Revalensia, 2015)
The present study is an inquiry into the text and context of the article “Vystavka v Akademii khudozhestv za 1860–61 god” (1861). As this article first appeared anonymously in the journal of the Dostoyevsky brothers, some Dostoyevsky scholars of the early 20th century attributed the article’s text to Fyodor Dostoyevsky. Later scholarship objected to this attribution, stressing the fact Dostoyevsky merely edited or co-authored the article’s text. In his study, Alexei Balakin reveals the true extent of Dostoyevsky’s contribution, proving that it is limited to two passages (one and a half pages).